2015
DOI: 10.1590/1089-68916i118730
|View full text |Cite
|
Sign up to set email alerts
|

Adubação Nitrogenada Em Capim-Massai: Morfogênese E Produção

Abstract: Resumo:Objetivou-se avaliar as características morfogênicas e estruturais bem como a produção de biomassa de plantas de Panicum maximum cv. Massai sob doses de nitrogênio. O experimento foi instalado em delineamento de blocos casualizados com quatro tratamentos (0, 80, 160 e 240 kg de N/ha) e quatro repetições, em parcelas de 4 m 2 . A adubação nitrogenada foi aplicada parceladamente, de acordo como os tratamentos. Plantas de capim-massai responderam linear e positivamente à adubação nitrogenada com aumento si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 11 publications
2
32
1
14
Order By: Relevance
“…The increase in the DMP of tropical pasture grass plants as a function of increasing doses of N was presented by Martuscello et al (2015) and Cunha et al (2012). According to Fagundes et al (2006), the supply of this nutrient is indispensable in pasture production systems, when N resulting from soil organic matter mineralization is not sufficient Figure 2.…”
Section: Resultsmentioning
confidence: 90%
“…The increase in the DMP of tropical pasture grass plants as a function of increasing doses of N was presented by Martuscello et al (2015) and Cunha et al (2012). According to Fagundes et al (2006), the supply of this nutrient is indispensable in pasture production systems, when N resulting from soil organic matter mineralization is not sufficient Figure 2.…”
Section: Resultsmentioning
confidence: 90%
“…In 1PER, lower LSR values were registered, which might have occurred due to a higher contribution of N at the beginning of 1PER; therefore, plants increased their LER and LAR without the need to translocate N from older leaves to the growing shoots, influencing LSR reductions. However, Masturcello et al (2015) observed a significant increase in LSR as N doses increased. According to these authors, plants facing N scarcity can present low LSR to keep tissues alive as metabolism decreases.…”
Section: As Shown Inmentioning
confidence: 82%
“…Patês et al (2007), studying nitrogen effects on Tanzania grass, observed signifi cant results (0.17 leaves.day -1 ) by applying 100 kg.ha -1 . Additionally, Masturcello et al (2015), assessing the effect of nitrogen doses on massai grass in the northeastern region of Brazil, reported a LAR of 0.8 leaves.tiller -1 for a rate of 80-kg.ha -1 . According to the authors, these inferior results might have occurred due to little rainfall, typical of that region, what directly infl uences plant morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martuscello et al (2015) reported a high potential response to nitrogen fertilization in Massai grass. However, increased forage production may be limited by low base saturation, when not corrected by liming.…”
Section: Key-wordsmentioning
confidence: 99%